PECULIARITIES OF FUNCTIONING MECHANISM OF INVESTMENT MARKET IN UKRAINE - Халатур, С. М. (Scientific Progress & Innovations, 2013)
The nature and characteristics of the functioning mechanism of the investment market, the legal and institutional basis of regulation, the increasing of capacity mechanisms to ensure a favorable investment climate in Ukraine are examined. Two approaches to determine the place and role of investment in economic system that is directly related to the definition of “investment market” have been generalized. There has been defined that one of the priorities of economic policy in Ukraine is to stimulate investment, which is closely connected with the evaluation of the prediction of the investment market.